Thiodiketopiperazines and Alkane Derivatives Produced by the Mangrove Sediment–Derived Fungus Penicillium ludwigii SCSIO 41408 - Cai, Jian; Wang, Xueni; Yang, Zaizhun; Tan, Yanhui; Peng, Bo; Liu, Yonghong; Zhou, Xuefeng (Frontiers in Microbiology, 2022)
A new trithiodiketopiperazine derivative, adametizine C (1), and five new alkane derivatives (7–11), were isolated from the mangrove sediment-derived fungus Penicillium ludwigii SCSIO 41408, together with five known dithiodiketopiperazine derivatives (2–6). Their structures were elucidated on the basis of spectroscopic analysis and the absolute conﬁguration of 1 was determined by X-ray crystallographic analysis. In a variety of bioactivity screening, 1–5 exhibited some selective antifungal or antibacterial activities. Trithiodiketopiperazines 1–3 showed cytotoxicity against prostate cancer cell line 22Rv1 with IC50 values of 13.0–13.9 μM, moreover, 3 showed obvious activity against another prostate cancer PC-3 cells with IC50 value of 5.1 μM. Further experiments revealed that 3 could significantly reduce PC-3 cells colony formation and induce apoptosis in a dose-dependent manner. Several compounds also exhibited obvious inhibitory activities of lipopolysaccharide (LPS)-induced nuclear factor-κB (NF-κB) with IC50 values range from 8.2 to 21.5 μM, and 1, 5, and 9 were further evaluated for its effects on RANKL-induced osteoclastogenesis. Adametizine C (1), with the strongest inhibitory activity against RANKL-induced osteoclast differentiation in bone marrow macrophages cells with 10 μM, was suggested to be the promising lead compound for the treatment of osteoclast-related diseases.